Hymenobacter terrestris sp. nov. and Hymenobacter lapidiphilus sp. nov., isolated from regoliths in Antarctica. Issue 12 (6th December 2020) - Sedláček, Ivo; Pantůček, Roman; Zeman, Michal; Holochová, Pavla; Šedo, Ondrej; Staňková, Eva; Švec, Pavel; Králová, Stanislava; Vídeňská, Petra; Micenková, Lenka; Urvashi; Korpole, Suresh; et al.
Abstract : A group of four psychrotrophic bacterial strains was isolated on James Ross Island (Antarctica) in 2013. All isolates, originating from different soil samples, were collected from the ice-free northern part of the island. They were rod-shaped, Gram-stain-negative, and produced moderately slimy red-pink pigmented colonies on R2A agar. A polyphasic taxonomic approach based on 16S rRNA gene sequencing, whole-genome sequencing, MALDI-TOF MS, rep-PCR analyses, chemotaxonomic methods and extensive biotyping was used to clarify the taxonomic position of these isolates. Phylogenetic analysis based on 16S rRNA gene sequences showed that the isolates belonged to the genus Hymenobacter . The closest relative was Hymenobacter humicola CCM 8763 T, exhibiting 98.3 and 98.9% 16S rRNA pairwise similarity with the reference isolates P5342 T and P5252 T, respectively. Average nucleotide identity, digital DNA–DNA hybridization and core gene distances calculated from the whole-genome sequencing data confirmed that P5252 T and P5342 T represent two distinct Hymenobacter species. The menaquinone systems of both strains contained MK-7 as the major respiratory quinone. The predominant polar lipids for both strains were phosphatidylethanolamine and one unidentified glycolipid. The major components in the cellular fatty acid composition were summed feature 3 (C16:1 ω 7 c /C16:1 ω6 c ), C16:1 ω5 c, summed feature 4 (anteiso-C17:1 B/iso-C17:1 I), anteiso-C15:0 and iso-C15 : 0 for all isolates. Based on the obtained results, two novel species are proposed, for which the names Hymenobacter terrestris sp. nov. (type strain P5252 T =CCM 8765 T =LMG 31495 T ) and Hymenobacter lapidiphilus sp. nov. (type strain P5342 T =CCM 8764 T =LMG 30613 T ) are suggested.